A Systematic Review of Community of Practice (CoP) in Informal Learning Communities of English Teachers and Learners - Iswati, Luluk (Universitas Pahlawan Tuanku Tambusai, 2025)
Communities of Practice (CoP) have gained notice in informal learning communities. A substantial number of studies examine the employment of CoP to facilitate collective learning. However, little is known about its implementation for English language teachers or learners. In this study, 20 studies conducted between 2019 and 2023 on CoP that involved either English teachers or learners were systematically reviewed to offer a new understanding of this specific context. An analysis was comprehensively done to reveal the research context, interaction mode, activities, and challenges. The findings uncovered that most of the analyzed studies were conducted in an EFL (English as a Foreign Language) context. Three kinds of approaches have been adopted in running the learning communities: on-site, online, and blended mode. Various activities were also employed to facilitate collective learning in communities. In addition, challenges during interaction within communities are discussed. Based on the analyses, pedagogical implications and research areas that demand more investigation are also addressed.